MATERIALS FOR A REVISION OF LAURACEAE II - a. j. g. h. kostermans (BRIN Publishing (Penerbit BRIN), 1969)
New species are described in Actinodaphne (2), Beilschmiedia (1), Cinnamomum (14), Endiamdra (20), Lindera (1), Litsea (8). New combinations are made in Cinnamomum (2), Litsea (2), Neolitsea (1). New names are proposed in Persea (2), Beilschmiedia (1). One variety is created in Cryptocarya. Endiandra fragrans Allen is reinstated. Reductions, are made in Actinodaphne (2), Beilschmiedia (2), Cryptocarya (15), Endiandra, (6), Endlicheria (1), Haasia (1), Lindera (3), Litsea (41), Persea (1), Phoebe (1), Tetranthera (12). New records are cited for most species. First record of Caryodaphnopsis tonkinensis from New Guinea.